Taxonomic notes on the genus Satyrium Scudder, 1876 (Lepidoptera, Lycaenidae) of Afghanistan with description of two new taxa - Krupitsky, Anatoly V.; Pljushtch, Igor G.; Pak, Oleg V. (Zootaxa, 2015)
А new species and a new subspecies of Satyrium Scudder, 1876 (subfamily Theclinae, tribe Eumaeini) from the subgenera Superflua Strand, 1910 and Armenia Dubatolov & Korshunov, 1984 respectively are described from Bamyan Province, Central Afghanistan—S. (S.) skrylniki sp. n. and S. (A.) hyrcanica bamiana ssp. n. The new species of Superflua belongs to the Iranian complex of species. It inhabits the territory of Afghanistan, being isolated from two other species of the subgenus known from the territory in question. The new subspecies of Armenia is also found in isolation both from the nominate subspecies and two Middle and Central Asian subspecies. Both findings clarify some aspects of zoogeography of the Central Afghanistan mountains.